2002
DOI: 10.1074/jbc.m111750200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Use of Myristoyl Groups on Neuronal Calcium Sensor Proteins as a Determinant of Spatio-temporal Aspects of Ca2+ Signal Transduction

Abstract: The localizations of three members of the neuronal calcium sensor (NCS) family were studied in HeLa cells. Using hippocalcin-EYFP and NCS-1-ECFP, it was found that their localization differed dramatically in resting cells. NCS-1 had a distinct predominantly perinuclear localization (similar to trans-Golgi markers), whereas hippocalcin was present diffusely throughout the cell. Upon the elevation of intracellular Ca 2؉ , hippocalcin rapidly translocated to the same perinuclear compartment as NCS-1. Another memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
154
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(168 citation statements)
references
References 47 publications
10
154
4
Order By: Relevance
“…In some cases, the membrane association conferred by these moieties is dynamically regulated by Ca 2þ binding when a sequestered mysristoyl chain becomes solvent-exposed following a Ca 2þ -driven shift in conformation as originally described for recoverin (Ames et al 1997). VSNL proteins are also cytosolic at resting [Ca 2þ ] i but localize to the plasma membrane or Golgi complex upon Ca 2þ elevation (O'Callaghan et al 2002;Spilker et al 2002;O'Callaghan et al 2003b). Each of the NCS proteins displays distinct subcellular localizations, which are in part determined by additional interactions with specific phosphoinositides mediated by basic aminoterminal residues immediately proximal to the site of acylation (O'Callaghan et al 2003a;O'Callaghan et al 2005).…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 94%
See 2 more Smart Citations
“…In some cases, the membrane association conferred by these moieties is dynamically regulated by Ca 2þ binding when a sequestered mysristoyl chain becomes solvent-exposed following a Ca 2þ -driven shift in conformation as originally described for recoverin (Ames et al 1997). VSNL proteins are also cytosolic at resting [Ca 2þ ] i but localize to the plasma membrane or Golgi complex upon Ca 2þ elevation (O'Callaghan et al 2002;Spilker et al 2002;O'Callaghan et al 2003b). Each of the NCS proteins displays distinct subcellular localizations, which are in part determined by additional interactions with specific phosphoinositides mediated by basic aminoterminal residues immediately proximal to the site of acylation (O'Callaghan et al 2003a;O'Callaghan et al 2005).…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 94%
“…It displays a high Ca 2þ -binding affinity and is able to respond to small fluctuations in [Ca 2þ ] i . NCS-1 is amino-terminally myristoylated and is constitutively associated with membranes including plasma and Golgi membranes (O'Callaghan et al 2002), although in some cell lines, NCS-1 has been found to be partially cytosolic (de Barry et al 2006) and it is able to rapidly exchange between membrane and cytosolic pools (Handley et al 2010). In contrast to all other NCS family members, NCS-1 is not neuron specific and is expressed in neuroendocrine cells (McFerran et al 1998) and at low levels in several nonneuronal cell types.…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-rhod-1 was imaged using the Leica TCS-SP-MP microscope with excitation at 543 nm and light collection at 600 -650 nm. X-rhod-1 was used in the study of PC12 cells rather than Fura Red (22), since the latter dye could not be successfully loaded into PC12 cells, and other dyes were not compatible with measurements in EYFP-expressing cells. The X-rhod-1 fluorescence was diffusely and uniformly distributed, suggesting cytosolic localization of the probe.…”
Section: Methodsmentioning
confidence: 99%
“…N-terminal myristoylation of NCS-1 is thought to be important for protein structure, cellular localization [14], and function [15]. Myristoylation mediates structural changes in NCS-1 that increase its stability and affect the unfolding pathway of the protein [16].…”
Section: Introductionmentioning
confidence: 99%